Pembelajaran PPKn Berbasis Proyek dalam Membentuk Profil Pelajar Pancasila di SMPN 5 Tulungagung - Aprilia Eka Ardinta; Hikmah Eva Trisnantari (Jurnal Simki Postgraduate, 2024)
This study aims to determine the implementation and evaluation of project-based Civics learning in shaping the profile of Pancasila students. This type of research is qualitative research with observation research methods, interviews, and documentation. Researchers used data analysis techniques using the approach developed by Miles and Huberman include data reduction, data presentation, and conclusion drawing. The results of this study indicate that the implementation of project-based learning uses six steps according to its syntax including determining fundamental questions, designing project planning, preparing schedules, monitoring students and project progress, testing results, and evaluating experiences. To form the profile of Pancasila learners through project-based learning, teachers give project assignments in groups that begin with a question. Evaluation of project-based learning uses non-test evaluation tools carried out by direct observation.